UJI DAYA TERIMA AGAR-AGAR KOMBINASI LIDAH BUAYA (Aloe vera L.)DENGAN DAUN AFRIKA SELATAN(Vernonia amygdalina Delile) - Nazrah Elida Pohan; Evawany Y Aritonang; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Plain agar-agar can be fortified with antioxidants to supply the needs of antioxidants for people with Aloe vera leaf and South Africa leaf. They arevery rich in antioxidants, but the taste are bitter, so that the people are reluctant to consume them. The purpose of this research is to know the acceptance test of agar-agar with combination of Aloe vera leaf andSouth Africa leaf based on an analysis organoleptic including color, smell, taste and texture. This research is experimental research in manufacture of agar-agar with a combination of Aloe vera leaf and South Africa leaf with three comparisons, that are A1(90 gramsAloe vera leaf, 3 gramsSouth Africa leaf and 7 grams agar-agar powder), A2 (89 gramsAloe vera leaf, 4 gramsSouth Africa leaf and 7 grams agar-agar powder), and A3 (88 gramsAloe vera leaf, 5 gramsSouth Africa leaf and 7 grams agar-agar powder). Panelists in this research are students of the Public Health Faculty in University of Sumatra Utara as many as 30 people by using hedonic test and are analyzed by Anova test. The research results showed A1 has produced the dark brown color, unique smell and sweet taste of palm sugar and pandan leaf and the texture is dense solid gel. In A2 has produced rather young brown color, unique smell is slightly and taste is medium of palm sugar and pandan leaf and the dense texture. In A3 has produced rather greenish young brown color, unique smell and sweet taste of palm sugar and slightly bitter from the unique of South Africa leaf and dense texture. Results of hedonic tests which is conducted is obtained the highest percentage, that is A1 with a 81.1% color, 93.3% smell, 88.9 % taste and 86.7% texture. Wherease, by Anova test is obtained F-count (0,62 color; 4,69 smell; 9,95 flavour ;0,16 textures), which means no significant difference of color and texture of every treatment, but there are significant difference of the smell and flavor of every treatment. It can be concluded that the agar-agar with a combination of Aloe vera leaf and South Africa leaf in the treatment A1 is more preferred by the panelists. So that, it is recommended that the people can consume it as snack. Keywords: Agar-agar,Aloe Vera Leaf, South Africa Leaf